Mucosa of human detrusor impairs contraction and β‐adrenoceptor‐mediated relaxation. (13th August 2013) - Propping, Stefan; Wuest, Melinda; Eichhorn, Birgit; Wirth, Manfred P.; Kaumann, Alberto J.; Ravens, Ursula
Abstract : Objectives: To elucidate the impact of the mucosa on detrusor muscle function by investigating force of contraction under various stimulatory conditions and during subsequent relaxation using catecholamines. Patients and Methods: Detrusor tissue was obtained from patients who had undergone cystectomy for bladder cancer and strips of intact or mucosa‐denuded muscle were set up for force measurement. Preparations were precontracted with KCl, carbachol or electric‐field stimulation (EFS). Precontracted strips were relaxed using increasing concentrations of catecholamines in the absence and presence of the subtype‐selective β‐adrenoceptor (AR) blockers CGP 20712A (β1‐ARs), ICI 118, 551 (β2‐ARs), and L‐748, 337 (β3‐ARs). Results: Force development in response to KCl (40 mM), carbachol (1 μM) or EFS was larger in the absence of mucosa than in intact muscle strips. The force of contraction of mucosa‐denuded strips with detached urothelium incubated in the same chamber was as low as in intact strips. Noradrenaline relaxed precontracted detrusor strips to a significantly larger extent and at lower concentrations in denuded than in intact strips. CGP 20712A did not affect noradrenaline‐induced relaxation of denuded and intact strips, and ICI 118, 551 did not influence noradrenaline‐induced relaxation in denuded strips, but abolished the difference between denuded and intact strips. The antagonism of the relaxant effects of noradrenaline by L‐748, 337 was slightly smaller in intact than denuded strips. Conclusions: The mucosa of human detrusor strips impairs force development when stimulated with KCl, carbachol or EFS. The mucosa also blunts the relaxing effects of catecholamines. The latter effect does not involve the activation of β1‐ARs but only of β2‐ARs, whereas β3‐ARs mediate the relaxation of human detrusor.